PENGARUH INDEPENDENSI, KEAHLIAN AUDIT, PENGALAMAN DAN BESARAN FEE AUDIT TERHADAP KUALITAS AUDIT - Nidya Wulandari, Luh Gede Ayu; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 21 No 2 (2017)DO - 10.24843/EJA.2017.v21.i02.p03, 2017)
Professional auditor in conducting is an evaluation process performed by the auditor's audit reports on the use of funds or the budget. This research aimed to analyze the effect of independence, audit expertise, experience and the amount of audit fee to the quality of the audit process. This research was conducted at the office of the Bali Provincial Public Accountant with seven offices in 2016 with the auditors as many as 73 people as samples through the method of sample saturated. Data collected by distributing questionnaires and processed by multiple linear regression analysis. The analysis showed the independence, audit expertise, experience and audit fees have a positive influence on the quality of audit offices Public Accountant in Bali. Suggestions that can be recommended for the auditor needs to improve prudential principles in conducting the audit so that the auditor is able to find the errors made by the client.
Keywords: independence, audit expertise, experience, audit fees, audit quality